MicroRNAs Modulate Drug Resistance-Related Mechanisms in Hepatocellular Carcinoma - Liang, Yuehui; Liang, Qi; Qiao, Liang; Xiao, Fang (Frontiers in Oncology, 2020)
Liver cancer, one of the most common malignant tumors in the world, has posed serious threats to human health because of its high morbidity and mortality, rapid growth and strong invasiveness. Development of resistance to chemotherapy has raised concern in recent years partly due to the high-level heterogeneity of individual response to treatment. microRNAs (miRNAs) are emerging as master regulators of normal physiology and tumor-related pathological processes recently, and new researches have been reported miRNAs play a non-negligible role in liver cancer drug resistance. In order to clarify the role of miRNAs in drug resistance in detail, we reviewed the latest studies on chemotherapy resistance involved in hepatocellular carcinoma (HCC) from different regulation mechanisms including autophagy, membrane transporters, epithelial-mesenchymal transitions (EMT), tumor microenvironment, and genes and proteins that associated with apoptosis. By exploring the role of miRNAs in modulating drug resistance-related mechanisms in HCC, the current review will provide the basis for further elucidating the relationship between cancer genetics and therapeutic sensitivity.